Acute, Subacute, and Genotoxicity Assessments of a Proprietary Blend of Garcinia mangostana Fruit Rind and Cinnamomum tamala Leaf Extracts (CinDura®). (30th July 2020) - Dodda, Sundararaju; Alluri, Venkata Krishnaraju; Golakoti, Trimurtulu; Sengupta, Krishanu
Abstract : The present communication describes a battery of toxicity studies that include an acute oral toxicity, a subacute twenty-eight-day repeated oral dose toxicity, and genotoxicity studies on a herbal formulation CinDura® (GMCT). This proprietary herbal composition contains the extracts of the Garcinia mangostana fruit rind (GM) and the Cinnamomum tamala leaf (CT). The toxicological evaluations were performed following the Organization for Economic Cooperation and Development (OECD) guidelines. The acute oral toxicity study in Wistar rats suggests that the median lethal dose of CinDura® is at least 2000 mg/kg body weight. Acute dermal and eye irritation tests in New Zealand white rabbits indicate that the test item is nonirritant to the skin and eyes. A twenty-eight-day repeated dose oral toxicity study was conducted in male and female Wistar rats using daily doses of 250, 500, and 1000 mg/kg body weight, followed by a fourteen-day reversal period for two satellite groups. The CinDura®-supplemented animals did not show any sign of toxicity on their body weights, organ weights, and on the hematobiochemical parameters. The gross pathology and histopathological examinations indicated no treatment-related changes in the experimental animals. Overall, the no-observed-adverse-effect level (NOAEL) of the herbal blend is 1000 mg/kg body weight, the highest tested dose. Also, the results of the bacterial reverse mutation test and the erythrocyte micronucleus assay in mouse bone marrow suggest that CinDura® (GMCT) is neither mutagenic nor clastogenic.